Method for producing lithium nickel composite oxide
Patent Information
- Application Number
- JP2021548380
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-07-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-07-21
Smart Images

Figure 0007645464000002 
Figure 0007645464000003 
Figure 0007645464000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a lithium nickel composite oxide. [Background technology]
[0002] A secondary battery, such as a lithium ion secondary battery, includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode contains a lithium-containing composite oxide as a positive electrode active material. For example, lithium nickel oxide, which is advantageous for increasing capacity, is used as the lithium-containing composite oxide, and nickel is partially replaced with a different metal in order to further improve battery performance.
[0003] Patent Document 1 discloses a method for producing a lithium-nickel composite oxide, which includes continuously or intermittently supplying a plurality of molded bodies obtained by molding a mixture containing powders of a nickel-containing compound and a lithium-containing compound into a vertical furnace from an upper part of the furnace, sintering the molded bodies in the vertical furnace, and continuously or intermittently discharging the plurality of sintered molded bodies from a lower part of the vertical furnace to the outside. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-99406 A Summary of the Invention
[0005] In the manufacturing method described in Patent Document 1, when a large amount of molded bodies are supplied into a furnace, gas convection in the furnace is difficult and heat is difficult to transfer to the molded bodies, which can result in a decrease in crystallinity of the fired body.
[0006] One aspect of the present disclosure relates to a method for producing a lithium nickel composite oxide, the method including a step of sintering a molded body of a mixture containing a lithium-containing compound and a nickel-containing compound in a container to obtain a sintered body, wherein a void ratio occupied by gaps in the molded body in the container is 0.375 or more.
[0007] Another aspect of the present disclosure relates to a method for producing a lithium nickel composite oxide, comprising the step of sintering a molded body of a mixture containing a lithium-containing compound and a nickel-containing compound in a container to obtain a sintered body, wherein the molded body has a maximum length L of 11 mm or more, a minimum length h of 10 mm or more, and a ratio of the minimum length h of the molded body to the maximum length L: h / L of 0.4 or more.
[0008] According to the present disclosure, a lithium nickel composite oxide having high crystallinity can be efficiently obtained. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a conceptual diagram showing a molded body in a container before firing. [Diagram 2] FIG. 2 is a diagram showing a method for determining the aspect ratio. [Diagram 3] FIG. 3 is a schematic perspective view of a prismatic secondary battery with a portion cut away. [Figure 4] FIG. 4 is a diagram showing the relationship between the void ratio and the crystallinity (crystallite size) of the lithium nickel composite oxide. [Diagram 5] FIG. 5 is a diagram showing the relationship between the space ratio and the aspect ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A method for producing a lithium nickel composite oxide according to an embodiment of the present disclosure includes a step of sintering a compact of a mixture containing a lithium-containing compound and a nickel-containing compound in a container to obtain a sintered body (i.e., a lithium nickel composite oxide). However, the void ratio occupied by gaps in the compact in the container (hereinafter simply referred to as "void ratio") is set to 0.375 or more (condition 1). Alternatively, a compact is used that has a maximum length L of 11 mm or more, a minimum length h of 10 mm or more, and an aspect ratio of the minimum length h to the maximum length L: h / L of 0.4 or more (condition 2).
[0011] When at least one of Condition 1 and Condition 2 is satisfied, gas convection in the gaps between the compacts is promoted, which promotes heat conduction to the compacts and facilitates sintering of the compacts. In addition, by promoting gas convection in the gaps between the compacts, unnecessary gas (mainly moisture) generated as sintering progresses is easily released to the outside, suppressing the effect of moisture on the compacts. As a result, the crystallinity of the sintered body is improved.
[0012] In addition, by using a molded body, the number of contact points between particles in the molded body increases, the thermal conductivity of the molded body improves, and this is advantageous for the progress of sintering. However, if the moisture generated from the molded body during sintering is difficult to release to the outside, the moisture remains in the molded body, and a part of the molded body collapses to generate sparse parts, resulting in insufficient contact between the particles and a decrease in the thermal conductivity of the molded body. In addition, the occurrence of sparse parts and dense parts tends to cause the degree of sintering to vary. In order to avoid such problems and improve the crystallinity of the lithium nickel composite oxide, it is important to promote gas convection in the gaps between the molded bodies.
[0013] According to the manufacturing method of this embodiment, the crystallite size of the lithium nickel composite oxide can be increased to, for example, 140 nm or more, and can also be increased to 160 nm or more or 170 nm or more. To determine the crystallite size of the lithium nickel composite oxide, first, X-ray diffraction (XRD) measurement is performed on the lithium nickel composite oxide to obtain an X-ray diffraction pattern. The obtained X-ray diffraction pattern is fitted by the WPPF (Whole-powder-pattern fitting) method using all diffraction peaks present between 2θ=10° to 120°. The crystallite size is calculated based on the result.
[0014] In condition 1, the void ratio needs only to be 0.375 or more, but in order to increase the crystallite size of the lithium nickel composite oxide, it is desirable for the void ratio to be 0.400 or more, and it may be 0.420 or more or 0.440 or more. On the other hand, by setting the void ratio to 0.600 or less, a sufficient amount of the molded body that can be accommodated in the container can be secured, so that the efficiency of the firing is improved and the lithium nickel composite oxide can be produced efficiently.
[0015] In Condition 2, the void ratio tends to increase as the maximum length L and the aspect ratio increase. In other words, in order to improve the void ratio and promote gas convection in the gaps between the compacts, it is important to control parameters such as the maximum length L and the aspect ratio of the compacts.
[0016] The maximum length L of the molded body may be, for example, 25 mm or more, or 28 mm or more. By using such large molded bodies, gas convection in the gaps between the molded bodies is further promoted. On the other hand, from the viewpoint of more quickly progressing the sintering of the center of the molded body, the maximum length L of the molded body may be, for example, 60 mm or less, or 40 mm or less.
[0017] Here, the void ratio refers to the ratio of the volume v1 of the space occupied by gaps in the compact to the volume V of the "apparent space" occupied by the compact, regardless of the depth of the container. The volume V of the apparent space is the sum of the actual volume v2 of the compact and the volume v1 of the gaps. The void ratio Rs is expressed by the following formula. Here, d is the bulk density obtained by dividing the total mass of the compacts filled in the container by the volume V of the apparent space, and D is the true density of the compact.
[0018] Rs=1-v2 / V=1-d / D With reference to Fig. 1(a), the apparent space occupied by the molded body is the space from the inner bottom surface of the container 20 to the filling level LU of the molded body 10. The shaded area in Fig. 1(b) indicates the space s1 occupied by the gaps of the molded body 10, and its volume is v1. The shaded area in Fig. 1(c) indicates the space actually occupied by the molded body 10, and its volume is v2. The shaded area in Fig. 1(d) indicates the apparent space S0, and its volume is V (=v1+v2).
[0019] The maximum length L and minimum length h of the molded body 10 are determined from the smallest rectangular parallelepiped circumscribing the molded body. Of all the sides of the six quadrilaterals constituting the smallest rectangular parallelepiped, the length of the longest side is the maximum length L. On the other hand, of all the sides, the length of the shortest side is the minimum length h. As shown in FIG. 2, when the smallest rectangular parallelepiped 30 circumscribing the molded body 10 is defined, the maximum length L, width w, and minimum length (height) h are determined, and the aspect ratio: h / L can be calculated.
[0020] The maximum length L and the minimum length h of the molded body may be, for example, the average value of the maximum length L and the minimum length h of 10 arbitrary molded bodies. The aspect ratio may also be the average value of the aspect ratios of 10 arbitrary molded bodies.
[0021] When the compact is fired at, for example, 600°C or higher and 850°C or lower, a fired body (lithium nickel composite oxide) can be obtained. The firing time may be, for example, 2 hours or longer and 30 hours or shorter. The firing is usually carried out in an oxidizing atmosphere containing oxygen or the like. The oxidizing atmosphere may be air or an atmosphere with a higher oxygen partial pressure than air. The oxygen concentration of the oxidizing atmosphere is, for example, 20% or higher.
[0022] The firing is carried out by filling a plurality of compacts in a specified container and supplying an oxidizing gas into the container. Even when a large number of compacts are filled in the container, if sufficient gaps are formed between the compacts, the oxidizing gas can be distributed throughout all of the compacts. Therefore, a large amount of homogeneous fired bodies can be produced.
[0023] When the mixture (powder) is fired without compression molding, it is difficult to perform firing uniformly because the powder is scattered by the supply of oxidizing gas and the molten material accumulates at the bottom of the container during firing. On the other hand, in the case of a molded body, the above problems are avoided, the shape of the molded body is maintained even after firing, and a fired body having almost the same shape as the molded body is obtained.
[0024] Considering durability against high temperatures, the material of the container is preferably ceramics, metals such as stainless steel, etc. The container usually has an open top and has a bottom and side surfaces rising from the periphery of the bottom.
[0025] When the molded body is fired in a container, the smaller the depth of the container, the more the gas convection near the bottom of the container is promoted. The depth of the container may be, for example, 300 mm or less, or 200 mm or less, in terms of significantly promoting heat conduction to the molded body and facilitating the release of unnecessary gas to the outside. The depth of the container refers to the height of the space inside the container that can accommodate the molded body. In addition, from the viewpoint of efficiently firing the molded body, it is desirable to be able to fill a certain amount of the molded body in the container. Therefore, the depth of the container may be, for example, 20 mm or more, or 100 mm or more. If the depth of the container is set as described above, the firing of the molded body will proceed sufficiently even if the height from the bottom of the container to the filling level LU of the molded body is, for example, 90% or more of the depth of the container.
[0026] From the viewpoint of facilitating handling of the molded body in the firing process of the molded body, the container may have a shape of, for example, a length of 100 mm to 500 mm and a width of 100 mm to 500 mm. Since such a container has an internal space of a substantially rectangular parallelepiped, it can be efficiently accommodated in a firing furnace.
[0027] The firing furnace may be of either a vertical or horizontal type, and for example, a tunnel-type horizontal firing furnace can be used.
[0028] The molded body can be obtained, for example, by compression molding a mixture containing a lithium-containing compound and a nickel-containing compound. The shape of the molded body is not particularly limited, but may be, for example, a sphere, an elliptical sphere (spheroid), a cylinder, an elliptical cylinder, a prism, a disk, an almond, or the like, in terms of being easily heated efficiently and uniformly. Compression molding can be performed, for example, using a briquette molding machine, a pellet molding machine, a granulator, a tablet press, or the like.
[0029] It is preferable that the compression molding is carried out in a dry manner. In the dry compression molding, the mixture is compression molded without adding a dispersion medium such as water.
[0030] The density of the molded body is, for example, 1.5 g / cm 3 More than 2.2g / cm 3 The density of the molded body is preferably 1.5 g / cm or less. 3 When the density of the compact is 2.2 g / cm or more, the particles constituting the compact can be brought into sufficient contact (adhesion) with each other, and the reaction between the particles can easily proceed. 3 When it is equal to or less than this, voids are appropriately formed inside the molded body, an oxidizing gas such as oxygen can be easily supplied to the inside of the molded body, and variation in the degree of sintering of the molded body can be easily suppressed.
[0031] The mixture containing the lithium-containing compound and the nickel-containing compound used for producing the molded body can be obtained by dry mixing the lithium-containing compound and the nickel-containing compound. That is, when mixing the lithium-containing compound and the nickel-containing compound, it is preferable to mix them without adding a dispersion medium such as water.
[0032] The lithium-containing compound may be lithium hydroxide, lithium oxide, lithium carbonate, etc. Among them, lithium hydroxide has high reactivity with nickel-containing compounds and is advantageous for improving the crystallinity of the lithium nickel composite oxide.
[0033] Lithium hydroxide is usually in a powder form, and the average particle size of lithium hydroxide (D50: particle size at 50% cumulative volume measured by a laser diffraction particle size distribution measuring device) is, for example, 10 μm or more and 500 μm or less.
[0034] When lithium hydroxide is used, it is preferable to heat-dry the lithium hydroxide in advance. When lithium hydroxide is heat-dried, the release of water during firing of the molded body is suppressed, and a lithium nickel composite oxide with high crystallinity is easily obtained.
[0035] The heating temperature of lithium hydroxide is preferably 100°C or higher and the melting point or lower. At 100°C or higher, the moisture contained in lithium hydroxide can be efficiently removed. When the heating temperature is lower than the melting point, the particle shape of lithium hydroxide is maintained, workability is improved, and a homogeneous mixture of the lithium-containing compound and the nickel-containing compound is easily obtained. The heating time of lithium hydroxide is, for example, 1 hour or more and 10 hours or less. The heating of lithium hydroxide may be performed in the air, but is preferably performed in a non-oxidizing atmosphere containing nitrogen, argon, or the like.
[0036] Examples of nickel-containing compounds include nickel hydroxide, nickel oxide, nickel sulfate, nickel nitrate, nickel carbonate, and nickel oxalate. The nickel-containing compound may contain a metal M1 other than lithium and nickel. For example, a composite hydroxide containing nickel and a metal M1 (hereinafter also referred to as hydroxide A) or a composite oxide containing nickel and a metal M1 (hereinafter also referred to as composite oxide B) may be used.
[0037] The composite oxide B can be obtained, for example, by heating the hydroxide A to 300°C or higher and 800°C or lower. By using the composite oxide B obtained by subjecting the hydroxide A to a heat treatment as the material for the molded body, the generation of water from the molded body during firing is suppressed. As a result, the decrease in the degree of contact between the lithium-containing compound and the composite oxide B and the decrease in the thermal conductivity of the molded body are suppressed, and the crystallinity of the fired body (lithium nickel composite oxide) is likely to be improved. Among these, it is preferable to use a mixture of lithium hydroxide and the composite oxide B for producing the molded body.
[0038] The composite oxide B includes a state in which a part of the Ni sites in the crystal lattice of nickel oxide is replaced with the metal M1, or a state in which the metal M1 is dissolved in the nickel oxide. When the heating temperature of the hydroxide A is within the above range, the composite oxide B can be obtained efficiently. The heating time of the hydroxide A is, for example, 30 minutes or more and 10 hours or less. The heating of the hydroxide A may be performed in a non-oxidizing atmosphere containing nitrogen or the like, or in an oxidizing atmosphere containing oxygen or the like. The oxidizing atmosphere may be air or an atmosphere with a higher oxygen partial pressure than air. The oxygen concentration of the oxidizing atmosphere is, for example, 20% or more.
[0039] The hydroxide A (composite hydroxide) can be produced by a known method such as a coprecipitation method. In the coprecipitation method, an alkali is added to an aqueous solution containing a nickel salt and a salt of a metal M1 to co-precipitate a composite hydroxide. Nickel sulfate or the like can be used as the nickel salt. When the metal M1 contains cobalt and aluminum, cobalt sulfate and aluminum sulfate or the like can be used as the salt of the metal M1. Sodium hydroxide or the like can be used as the alkali.
[0040] Nickel is advantageous for increasing the capacity and reducing the cost. Metal M1 preferably contains cobalt and also preferably contains a metal M2 other than cobalt. Cobalt is advantageous for extending the battery life. Metal M2 preferably contains at least aluminum. Aluminum is advantageous for improving the thermal stability. By using a lithium-containing composite oxide containing nickel, cobalt, and aluminum as a positive electrode active material, it becomes possible to increase the capacity and extend the life of the secondary battery.
[0041] From the viewpoint of stabilizing the crystal structure and the like, metal M2 may further contain at least one selected from the group consisting of manganese, tungsten, niobium, magnesium, zirconium, and zinc.
[0042] Hydroxide A preferably contains a composite hydroxide containing nickel, cobalt, and metal M2. When such a composite hydroxide is used, it is easy to uniformly disperse nickel, cobalt, and metal M2 in the molded body.
[0043] When the atomic ratio of nickel, cobalt, and metal M2 contained in hydroxide A is Ni:Co:M2 = (1 - x - y):x:y, x preferably satisfies 0 ≦ x < 0.15, more preferably 0.01 < x < 0.15, and y preferably satisfies 0.001 < y < 0.1. In this case, the effects of using nickel, cobalt, and metal M2 (or nickel and metal M2) can be obtained in a well-balanced manner.
[0044] The composite hydroxide obtained by the coprecipitation method can form secondary particles in which primary particles are aggregated. The average particle diameter (D50: the particle diameter at 50% cumulative volume measured by a laser diffraction particle size distribution analyzer) of the secondary particles of the composite hydroxide is, for example, 2 μm or more and 20 μm or less.
[0045] When a molded body of a mixture containing lithium hydroxide and composite oxide B is fired at 600 °C or higher and 850 °C or lower to obtain a lithium nickel composite oxide, a layered rock salt type lithium nickel composite oxide in which part of the nickel in lithium nickel oxide is substituted with metal M1 can be obtained. By substituting part of the nickel with metal M1, further improvement in battery performance becomes possible.
[0046] The lithium nickel composite oxide preferably has a composition represented by the formula: Li a Ni 1-x-y Co x M2 y O2. In the formula, a satisfies 0.9 < a < 1.1, x satisfies 0 ≦ x < 0.15, more preferably 0.01 < x < 0.15, and y satisfies 0.001 < y < 0.1. By using the lithium nickel composite oxide of the above composition as a positive electrode active material, a high-capacity and long-life secondary battery can be obtained.
[0047] When producing the lithium nickel composite oxide of the above composition, Ni 1-x-y Co x M2 y (OH)2 may be used as hydroxide A. Also, in the mixture used for manufacturing the molded body, lithium hydroxide and composite oxide B may be mixed so that the atomic ratio of lithium to the total of nickel and metal M1 in composite oxide B: Li / (Ni + M1) is more than 0.9 and less than 1.1.
[0048] The obtained fired body may be crushed into powder. Also, the powder may be classified to have a desired particle size distribution. For crushing the fired body, a ball mill, a mortar, etc. are used. For classification, a sieve, etc. are used.
[0049] The lithium nickel composite oxide can form secondary particles in which primary particles are aggregated. The average particle size (D50: the particle size at 50% cumulative volume measured by a laser diffraction particle size distribution measuring device) of the secondary particles of the lithium nickel composite oxide is, for example, 2 μm or more and 20 μm or less.
[0050] The lithium nickel composite oxide obtained by the above-mentioned production method is suitable for use as a positive electrode active material in a secondary battery. The secondary battery includes a positive electrode including a positive electrode active material capable of electrochemically absorbing and releasing lithium ions, a negative electrode including a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, and an electrolyte.
[0051] The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture includes a positive electrode active material as an essential component, and may include a binder, a conductive agent, and the like as optional components.
[0052] The negative electrode includes, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode mixture includes a negative electrode active material as an essential component and may include a binder, a thickener, and the like as optional components.
[0053] Examples of the negative electrode active material include carbon materials, silicon, silicon compounds, metallic lithium, lithium alloys, etc. Examples of the carbon material include graphite (natural graphite, artificial graphite, etc.), amorphous carbon, etc.
[0054] The electrolyte may be a liquid electrolyte in which a solute such as a lithium salt is dissolved in a solvent. As the solvent, a non-aqueous solvent may be used, and water may also be used. The electrolyte may also be a solid electrolyte.
[0055] Usually, a separator is interposed between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.
[0056] 3 is a schematic perspective view of a partially cut-away prismatic secondary battery. The battery includes a bottomed prismatic battery case 4, and an electrode group 1 and an electrolyte (not shown) housed in the battery case 4. The electrode group 1 is a wound type having a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them.
[0057] One end of a negative electrode lead 3 is attached to the negative electrode current collector of the negative electrode, and the other end is connected to a negative electrode terminal 6 provided on a sealing plate 5. The negative electrode terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of a positive electrode lead 2 is attached to the positive electrode current collector of the positive electrode, and the other end is connected to the back surface of the sealing plate 5. The opening of the battery case 4 is sealed by laser welding the periphery of the sealing plate 5 to the opening end. An electrolyte injection hole provided in the sealing plate 5 is closed by a plug 8.
[0058] Hereinafter, the present disclosure will be specifically described based on examples and comparative examples, but the present disclosure is not limited to the following examples.
[0059] Example 1 Lithium hydroxide monohydrate (average particle size (D50) 50 μm) was heated and dried at 150 ° C for 1 hour to prepare lithium hydroxide. 0.85 Co 0.12 Al 0.03 (OH)2 (average particle size (D50) of secondary particles is about 15 μm). 0.85 Co 0.12 Al 0.03 (OH)2 was heated in air at 700°C for 2 hours, and Ni 0.85 Co 0.12 Al 0.03 O was obtained. Lithium hydroxide and Ni 0.85 Co 0.12 Al 0.03 The mixture was dry-mixed with O such that the atomic ratio of Li to the total of Ni, Co and Al: Li / (Ni+Co+Al) was 1.05 / 1 to obtain a mixture.
[0060] The mixture was dry-compressed and molded using a briquette molding machine to obtain an almond-shaped compact (maximum length L = 28 mm, minimum length h = 13.7 mm, aspect ratio: h / L = 0.49). The density of the compact was 1.85 g / cm. 3 The compression force was adjusted so that
[0061] The obtained molded body was packed into a ceramic rectangular container with a length of 330 mm, a width of 330 mm, and a depth of 220 mm, and sintered at 750°C for 5 hours in an oxidizing atmosphere (oxygen concentration 99%) to obtain a sintered body (lithium nickel composite oxide) A1. At this time, the void ratio occupied by the gaps of the molded body in the container was 0.420. The height from the bottom of the container to the filling level LU of the molded body was 200 mm.
[0062] The composition of the obtained lithium nickel composite oxide was Li 1.05 Ni 0.85 Co 0.12 Al 0.03 The composition of the lithium nickel composite oxide was confirmed by ICP emission spectrometry.
[0063] Example 2 The mixture was dry-compressed and molded using another briquette molding machine to obtain an almond-shaped compact (maximum length L = 28 mm, minimum length h = 17 mm, aspect ratio: h / L = 0.61). The density of the compact was 1.85 g / cm 3 The compression force was adjusted so that the compaction level LU was 190 mm. A lithium nickel composite oxide A2 was obtained by the same method as in Example 1 except for the above. The void ratio of the gaps of the compacts in the container was 0.443. The height from the bottom of the container to the filling level LU of the compacts was 190 mm.
[0064] Comparative Example 1 Except for the fact that the mixture was fired as it was without compression molding, a lithium nickel composite oxide B1 was obtained in the same manner as in Example 1. The height from the bottom of the container to the filling level LU of the molded body was set to 190 mm.
[0065] Comparative Example 2 The mixture was dry compressed using a tablet press to obtain a cylindrical compact (maximum length L = 6 mm, minimum length h = 6 mm, aspect ratio: h / L = 1.0). The density of the compact was 1.6 g / cm 3The compression force was adjusted so that the compression force was regulated to 0.5 mm. A lithium nickel composite oxide B2 was obtained by the same method as in Example 1 except for the above. The void ratio of the gaps in the molded bodies in the container was 0.333. The height from the bottom of the container to the filling level LU of the molded bodies was 190 mm.
[0066] The crystallite sizes of the lithium nickel composite oxides A1, A2, B1, and B2 obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were determined by the method described above. The determined crystallite sizes are shown in Table 1.
[0067] [Table 1]
[0068] In the lithium nickel composite oxides obtained in Examples 1 and 2, the crystallite size was significantly increased to 160 nm or more compared to the lithium nickel composite oxides obtained in Comparative Examples 1 and 2. In Examples 1 and 2, it is considered that gas convection in the gaps between the compacts was promoted, heat conduction to the compacts was promoted, and sintering of the compacts proceeded sufficiently. In addition, it is considered that the unnecessary gas generated as the sintering proceeded was easily released to the outside, which also contributed to the improvement of the crystallinity of the sintered body.
[0069] On the other hand, in Comparative Examples 1 and 2, gas convection in the gaps between the compacts was insufficient, which is believed to have reduced the reactivity between lithium hydroxide and composite oxide B, resulting in reduced crystallinity of the fired body.
[0070] The relationship between the void ratio and the crystallinity of the lithium nickel composite oxide is shown in Figure 4. Figure 4 suggests that a void ratio of 0.375 or more is effective in achieving a crystallite size of 140 nm or more in the lithium nickel composite oxide.
[0071] Figure 5 shows the relationship between void ratio and aspect ratio. Here, the slope of the line was calculated from two data (A1, A2) for a maximum length L of 28 mm, and it was assumed that the slope would be the same when the maximum length L was 6 mm or 25 mm. The data for 25 mm is hypothetical data derived from the void ratio when the molded body is a sphere with an aspect ratio of 1.0. Figure 5 shows that the void ratio increases as the maximum length L and aspect ratio of the molded body increases. It can also be seen that even when the maximum length L is around 11 mm, a void ratio of 0.375 or more can be ensured by increasing the minimum length h to 10 mm or more (i.e., increasing the aspect ratio). [Industrial Applicability]
[0072] The lithium nickel composite oxide obtained by the production method according to the present disclosure is suitably used, for example, as a positive electrode active material for secondary batteries that require high capacity and high reliability. [Explanation of symbols]
[0073] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing
Claims
1. The method includes a step of filling a compact of a mixture containing a lithium-containing compound and a nickel-containing compound into a container and firing the compact in the container to obtain a fired body, The void ratio of the gaps of the molded body in the container is 0.400 or more (except for the case where the void ratio is 0.4764 or more), The maximum length L of the molded body is 11 mm or more, The minimum length h of the molded body is 10 mm or more, A method for producing a lithium nickel composite oxide, wherein a ratio of a minimum length h of the compact to a maximum length L of the compact: h / L is 0.4 or more.
2. The method for producing a lithium nickel composite oxide according to claim 1, wherein the molded body has a maximum length L of 25 mm or more.
3. The method for producing a lithium nickel composite oxide according to claim 1 or 2, wherein the depth of the container is 20 mm or more and 300 mm or less.
4. The method for producing a lithium nickel composite oxide according to claim 3, wherein the container has a length of 100 mm to 500 mm and a width of 100 mm to 500 mm.
5. The method for producing a lithium nickel composite oxide according to any one of claims 1 to 4, wherein the shape of the molded body is any one of a spherical shape, an oval spherical shape, and an almond shape.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method of manufacturing positive electrode active material, electrode for lithium secondary battery, and lithium secondary battery
JP2014063708A
Production method of lithium-nickel composite oxide and production method of nonaqueous electrolyte secondary battery
JP2019099406A
Nonaqueous electrolyte secondary battery positive electrode active material and method for producing same, and nonaqueous electrolyte secondary battery which uses positive electrode active material
WO2019087494A1